Strategies of Green Marketing as tool of Competitive Advantage - Ansari, Arslan Afzal; Ameer, Muhammad Waqas; Tabbassum, Lubna (Pakistan Journal of Humanities and Social Sciences, 2019)
This paper aims to find out the impact of green marketing strategies as tool of competitive advance for the firm. Green marketing is a basic tool and marketing strategy to get competitive advantage on other firms in the market. The firms which are going green are enjoying high returns and a great increase in their profits. Moreover these firms also have competitive advantage on other firms in the market.